The Incidence of Tooth Agenesis in Pediatric Patients in the Olomouc Region - L. Kramerová; P. Krejčí; E. Kaplová; K. Langová (Czech Dental Chamber, 2014)
Aim of the study: Many developmental anomalies can occur in craniofacial region. Dental developmental anomalies, namely hypodontia, are the most often of them. The prevalence of agenesis in permanent dentition (excluding third molars) in European population is 5,5%. The aim of our study was to determine the prevalence of agenesis of teeth except third molars in pediatric patients in the Olomouc Region, to compare its frequency in boys and girls, to determine the prevalence of agenesis of teeth of different morphological classes and to make comparisons with other available studies. Material and methods: The study was conducted from 1. 10. 2010 to 1. 2. 2013 at the Pediatric department of Institute of Dentistry and Oral Sciences of Faculty of Medicine and Dentistry of Palacký University Olomouc. It included 434 persons aged between eight and 19 years. Clinical and radiographical evaluations were carried out. Age, gender, systemic diseases, syndromes, number and localization of missing teeth were recorded. Results: Prevalence of agenesis of teeth except third molars was set at 12.04% for girls, at 7.41% for boys, at 9.45% for both sexes together. Only one or two teeth were missing in 85% of persons. The highest number of missing teeth was four, nobody showed agenesis of five or more teeth. The most often was the absence of lower second premolars, which was founded in 20 patients (prevalence 4.61%), followed by the upper lateral incisors (prevalence 3.69%) and upper second premolars (prevalence 2.53%). Conclusion: The two-year study showed the prevalence of tooth agenesis except third molars in pediatric patients in the Olomouc Region. The results were compared with Czech epidemiological investigations published in 1970s and with foreign studies. Most of the results were not significantly different.